Oxford Handbook of General Practice, 2nd Edition - Simon, Chantal, Everitt, Hazel; Kendrick, Tony (OXFORD UNIVERSITY PRESS, 2005)
This is the second edition of the Oxford Handbook of General PracticeÃ¢â‚¬â€ so what's changed? When we wrote the first edition, we spent many long hours debating what to include and what to exclude. It wasn't an easy task, as general practice has no boundaries and, inevitably, we excluded topics we should have included and vice versa. In this edition, we have updated the first edition material: we have completely rewritten the general practice section to include the new GP contract and updated clinical topics in line with new national and international guidelines. As a result of feedback from readers, we have tried to make the text clearer and more evidence-based. We have also included several new topics such as complementary medicine, elderly care, and chronic disease management, as well as expanding some of the preexisting sections. We have lost two of our authors. Jon Birtwistle has moved to a new post and no longer works in general practice. Brian Stevenson has retired and is enjoying life to the full travelling the world. In their place, we have gained Tony Kendrick, Professor of Primary Care at Southampton University, as a guest author for this edition. He has a special interest in mental health problems in primary care and has considerably updated that section in this edition, as well as providing invaluable feedback on many other sections.